Rivalry for nutrient resources : is there competition below ground between leguminous trees and grasses in a mesic and arid savanna in the Kruger National Park? - Shadwell, Eleanor (Department of Biological Sciences, 2017)
As described in the resource-based co-existence theory, trees and grasses are able to co-occur due to partitioning of the edaphic environment in savannas. This study describes the fine root-distribution of dominant leguminous C₃ trees and C₄ grasses relative to soil nitrogen, phosphorus and water profiles using stable carbon and nitrogen isotope ratios (of the fine roots). The study occurs on a mesic savanna (737 mm MAP) site on sandy-loam soils and an arid savanna (547 mm MAP) site on clay-rich soils in the Kruger National Park, South Africa. We show that most tree and grass roots are located in the upper layers of the soil and both are present to the bottom of the profile. Root biomass is positively correlated to soil nitrogen and phosphorus and negatively to soil moisture and there were significant differences between sites, but very few of the results were significantly different down the soil profile. Therefore, the niche-separation hypothesis was not supported. The Scheiter & Higgins (2007) model illustrates that even though rooting niche separation is not an essential precondition for grass-tree coexistence, competition in the rooting zone can shape patterns of tree dominance in savannas, which may help in dealing with the problem of bush encroachment in savannas.